(untitled) (Scientific journal of the Fergana State University, 2024)
The quantitative content of 32 macro and microelements was determined by neutron activation analysis, as well as the amino acid composition was studied by the analysis of FTK-derivaties of amino acids by HPLC method in the leaves and kernels of seeds Prunus persica var.nectarina growing in Uzbekistan.